Proanthocyanidin Synthesis in Chinese Bayberry (Myrica rubra Sieb. et Zucc.) Fruits - Shi, Liyu; Cao, Shifeng; Chen, Xin; Chen, Wei; Zheng, Yonghua; Yang, Zhenfeng (Frontiers in Plant Science, 2018)
Proanthocyanidins (PAs) are distributed widely in Chinese bayberry fruit and have been associated with human health benefits, but molecular and biochemical characterization of PA biosynthesis remains unclear. Here, two genes encoding key PA biosynthetic enzymes, anthocyanidin reductase (ANR) and leucoanthocyanidin reductase (LAR) were isolated in bayberry fruit. MrANR was highly expressed at the early stage of fruit development when soluble PAs accumulated at high levels. Meanwhile, the transcript abundance of both MrANR and MrLAR observed at the late stage was paralleled with the high amounts of insoluble PAs. LC-MS/MS showed that PAs in developing Chinese bayberry fruits were comprised predominantly of epigallocatechin-3-O-gallate terminal subunits, while the extension subunits were a mixture of epigallocatechin-3-O-gallate, epigallocatechin and catechin. Recombinant MrANR protein converted cyanidin to a mixture of epicatechin and catechin, and delphinidin to a mixture of epigallocatechin and gallocatechin in vitro. Recombinant MrLAR was active with leucocyanidin as substrate to produce catechin. Ectopic expression of MrANR in tobacco reduced anthocyanin levels but increased PA accumulation. The catechin and epicatechin contents in transgenic flowers overexpressed MrANR were significantly higher than those of wild-type. However, overexpression of MrLAR in tobacco led to an increase in catechin levels but had no impact on PA contents. Quantitative real time PCR revealed that the loss of anthocyanin in transgenic flowers overexpressed MrANR or MrLAR is probably attributed to decreased expression of tobacco chalcone isomerase (CHI) gene. Our results not only reveal in vivo and in vitro functions for ANR and LAR but also provide a resource for understanding the mechanism of PA biosynthesis in Chinese bayberry fruit.